Molecular cloning, characterization of Pomacea canaliculata HSP40 and its expression analysis under temperature change. (April 2019) - Xu, Yipeng; Zheng, Guowan; Liu, Guangfu; Yang, Qianqian; Yu, Xiaoping
Abstract: Heat shock proteins (HSPs) play important roles in the adaption of Pomacea canaliculata to unsuitable environments. In the present study, a cDNA encoding HSP40 in P. canaliculata ( Poca HSP40) was cloned and characterized. The Poca HSP40 cDNA was 1466 bp, containing an ORF of 954 bp encoding 317 amino acids. Bioinformatics analysis showed that Poca HSP40 belonged to type II HSP40s and had four predicted phosphorylation sites. Phylogenetic analysis proved the conservation of HSP40s in mollusks. Poca HSP40 was widely expressed in the gill, digestive gland, kidney, and foot muscle of P. canaliculata . Challenged by different temperatures, the expression of Poca HSP40 was up-regulated under low temperatures but not high temperatures, which was contrary to the expression change of Poca HSP70 under low and high temperatures. These results implied that P. canaliculata evolved different strategies for survival under low temperature and high temperature through the regulation of HSPs. Highlights: cDNA of P. canaliculata HSP40 ( Poca HSP40) was cloned and it belonged to type II HSP40s. Poca HSP40 was widely expressed in P. canaliculata, and its expression was up-regulated when challenged by low temperature. P. canaliculata might evolve different strategies for survival under low and high temperature by regulating HSPs expression.